1995
DOI: 10.1007/bf01874765
|View full text |Cite
|
Sign up to set email alerts
|

The role of the seed tuber in determining partial resistance to potato blackleg caused byErwinia spp.

Abstract: In t991 and 1992, 12 potato cultivars were screened at two locations for resistance to blackleg, after vacuum infiltration of the seed with Erwinia carotovora subsp, atroseptica or E. chrysanthemi. Cultivar differences for resistance to E.c. subsp, atroseptica and E. chrysanthemi were found which were consistent over locations and years. Seed tubers of the same cultivars were also screened for resistance to both Erwinia spp. by using a tuber slice inoculation method. Correlation coefficients for comparisons be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In this study, contamination of progeny tubers with Eca may have occurred late in the growing season due to a slow built up of Eca populations in the mother tubers to levels high enough for invading stolons and, consequently, infection of progeny tubers. This is in agreement with the absence of Eca in progeny tubers of early potato cultivars, which show an rapid average mother tuber decay in the field, such as Alcmaria, Arinda and Venouska (Allefs et al, 1995). The contrary was found for the late potato cultivars Hertha, Karnico 6,69 + ----+-= positive reaclion, -~ negative reaction, '' The detection thresholds of dilution plating were > ID" and > 10^ cells/mi before and after enrichment, respectively.…”
Section: Relation Between Blaekleg Incidence and Transmission Of Ecasupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, contamination of progeny tubers with Eca may have occurred late in the growing season due to a slow built up of Eca populations in the mother tubers to levels high enough for invading stolons and, consequently, infection of progeny tubers. This is in agreement with the absence of Eca in progeny tubers of early potato cultivars, which show an rapid average mother tuber decay in the field, such as Alcmaria, Arinda and Venouska (Allefs et al, 1995). The contrary was found for the late potato cultivars Hertha, Karnico 6,69 + ----+-= positive reaclion, -~ negative reaction, '' The detection thresholds of dilution plating were > ID" and > 10^ cells/mi before and after enrichment, respectively.…”
Section: Relation Between Blaekleg Incidence and Transmission Of Ecasupporting
confidence: 88%
“…The results of blackleg development in the field of the cultivars tested were similar to those found by Allefs et al (1995). Cultivars Desiree, Arinda, Karnico and Producent were the most resistant, i.e.…”
Section: Relation Between Blaekleg Incidence and Transmission Of Ecasupporting
confidence: 82%
“…Several methods have been described for the screening of tuber tissue resistance (see Allefs et al, 1995a) or stem tissue resistance (Hidalgo & Echandi, 1982;Hossain & Logan, 1983;Wastie, 1984;Lapwood & Read, 1986). In a previous study (Allefs et al, 1995b), it was shown that tuber tissue resistance of stored tubers of a set of 12 cultivars was not very well correlated with resistance to blackleg. Resistance of mother tuber tissue as expressed during development and growth of plants in the field, however, seemed to be of importance.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present further evidence for the existence of a mechanism of resistance which is located in the stem base. Furthermore, we screened the same set of 12 cultivars for above-ground stem tissue resistance to Eca and Ech and studied the role of stem base resistance, stem tissue resistance, tuber tissue resistance (Allefs et al, 1995a, in press) and mother tuber decay in the field (Allefs et al, 1995b) as components in determining partial resistance to blackleg in the field. The consequences of the results for resistance breeding are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be related to the differences in resistance expression of the cultivar depending on the organ tested. Several authors noted that one of the difficulties in screening cultivars for resistance to pectinolytic Erwinia was related to the lack of correlation between stem and tuber resistance (Allefs et al, 1995), and to the different performance of inoculation methods, leading to different rankings of potato cultivars (Bain & Pérombelon, 1988). The difficulty of detecting the bacterium on diseased organs (stolons and tubers) by PCR could be explained by inappropriate storage of the samples.…”
Section: Discussionmentioning
confidence: 99%